PENGARUH KINERJA KEUANGAN TERHADAP MANAJEMEN LABA PERUSAHAAN YANG MELAKUKAN INITIAL PUBLIC OFFERING (IPO) - AFRIANDI, DEASHINTA DIAN (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
This research is meant to find out the indication of the existence of earnings management practices around Initial Public Offering (IPO) which starts from one year before IPO, during IPO, and One year after IPO. Afterthe company indicated to earnings management around the IPO, then the current ratio, debt to equity ratio, netprofit margin and asset turnover fixed tested their effects on earnings management in the form of discretionary accruals (DA). Secondary data is applied in this research.Â The samples which are used in this research are takenfrom the population of companies which perform IPO in the Indonesia Stock Exchange during 2008 â 2010periods. The multiple linear regressions analysis, one sample t-test and t test are applied as the data techniqueanalysis in this research. The results of this study show that: (1) during the IPO the company is indicated that ithas already been implementing earnings management, (2) independent variables such as current ratio and fixedasset turnover have no influence to the earnings management, while the companyâs financial performance whenit is seen from debt to equity ratio and net profit margin has an influence to the earnings management. Keywords:Â  Earnings Management, Initial Public Offering (IPO), Financial Performance.